Motyw listu w komediach Plauta - Jagiełło, Katarzyna (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The article presents an analysis of letters found in Plautus' comedies. Dividing the correspondence into that which is read and that which is not read on the stage and into the authentic and falsifed, presents its structures, studies its coherence and defnes dependencies between the type of a letter and the role it plays in the comedy.
The motif of letter in Plautus' comedies
Keywords: antique theatre; Palliata; Plautus; Motif of letter